Management of malperfusion: New York approach and outcomes. Issue 5 (19th September 2020) - Iannacone, Erin; Robinson, Bryce; Rahouma, Mohamed; Girardi, Leonard
Abstract: Background and Aim: Aortic branch malperfusion complicates up to one‐third of acute type A aortic dissection (ATAAD), and it is a strong predictor of poor outcomes. We analyzed our results for the surgical management of this high‐risk cohort. Methods: We queried our aortic database for consecutive patients undergoing ATAAD repair. Those presenting with malperfusion were compared with those without. Outcomes were compared using univariate and multivariate analysis. Results: From 1997 to 2019, a total of 336 patients underwent ATAAD repair. A total of 97 ATAAD patients presented with malperfusion. Malperfusion patients were more likely to be male (54.8% vs. 75.3%; p = .001), have had a prior myocardial infarction (11.9% vs. 26.8%; p = .001), to present with preoperative renal dysfunction (22.2% vs. 54.6%; p < .001), and to present with shock (12.6% vs. 28.9%; p = .001). The malperfusion group more often underwent coronary artery bypass grafting (5.4% vs. 24.7%; p < .001), and required additional noncardiac procedures 10.3% of the time. Operative mortality (0.8% vs. 15.5%; p < .001) and major adverse events (MAEs) (7.6% vs. 20.6%; p = .001) were both greater for the malperfusion patients. Ejection fraction, diabetes, and malperfusion were predictors of MAEs. Cerebral, coronary, mesenteric, and multiple vascular bed malperfusion were predictors of MAEs, while extremity, renal, and spinal were not. Conclusion: Improving outcomes for this high‐risk cohort requires rapid diagnosis and reversal of ischemia while minimizing the risk of aortic rupture, irrespective of the strategic approach.